Preparation method and application of composite hydrogen storage material based on NiV2S4 and magnesium hydride

By mixing NiV2S4 with magnesium hydride ball mill, a magnesium-based composite hydrogen storage material was prepared, which solved the problem of slow reaction speed of magnesium hydride and reduced material performance, and achieved a reduction in the hydrogen release temperature and the maintenance of hydrogen storage capacity, which significantly improved the circulation stability and hydrogen storage performance of the material.

CN119750663AActive Publication Date: 2025-04-04HENAN UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510098245.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-04
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

Magnesium hydride reacts slowly at room temperature and pressure, and the material performance decreases during hydrogen absorption and discharge, which limits the improvement of its hydrogen storage performance.

Method used

By mixing NiV2S4 with magnesium hydride ball mill, a magnesium-based composite hydrogen storage material was prepared. NiV2S4 is a structure of nanoflower-like particles accumulation, which is directly prepared by high-temperature hydrothermal method, which is used to reduce the hydrogen release temperature of magnesium hydride, reduce particle agglomeration and growth, and improve the circulation stability of the material and maintain hydrogen storage capacity.

Benefits of technology

The hydrogen discharge starting temperature of the composite hydrogen storage material was reduced by 138°C. After circulating at 300°C for 60 times, the capacity retention rate was greater than 90%, which significantly improved the hydrogen absorption and circulation stability of magnesium hydride.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a novel composite hydrogen storage material based on NiV2S4 and magnesium hydride, and belongs to the technical field of magnesium-based hydrogen storage materials. The hydrogen storage material is prepared by mixing magnesium hydride and NiV2S4 through a ball milling process. The preparation method comprises the following steps: firstly, uniformly dispersing nickel chloride hexahydrate, sodium orthovanadate and thiourea into water; and then transferring to a Teflon container, keeping at 150-180 DEG C for 12-24 hours, and washing and drying to obtain NiV2S4. And finally, carrying out ball milling on NiV2S4 and magnesium hydride to prepare the magnesium hydride composite hydrogen storage material based on NiV2S4. The composite hydrogen storage material has excellent performance, compared with ball-milled magnesium hydride, the initial hydrogen desorption temperature is reduced by 138 DEG C, the hydrogen desorption amount reaches 6.21 wt% at the temperature of 350 DEG C within 5 minutes, the hydrogen absorption amount reaches 4.8 wt% at the temperature of 150 DEG C within 20 minutes, and the capacity is larger than 90% after 60 times of circulation at the temperature of 300 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid hydrogen storage materials, and in particular relates to a magnesium-based composite hydrogen storage material based on NiV2S4 and magnesium hydride, and a preparation method and application thereof. Background Art

[0002] People are actively looking for clean and sustainable energy alternatives, and hydrogen energy has become the focus due to its high efficiency and environmentally friendly characteristics. Hydrogen combustion only produces water, so it has a wide range of application prospects in transportation, industry, electricity and other fields.

[0003] Solid-state hydrogen storage technology is the key to realizing hydrogen energy applications, and magnesium hydride (MgH2) is regarded as an ideal hydrogen storage material due to its high hydrogen storage capacity. However, there are some technical barriers to the practical use of magnesium hydride, such as slow reaction speed at room temperature and pressure, and the degradation of material performance during the absorption and desorption of hydrogen. In order to improve the performance of magnesium hydride, scientists are trying a variety of strategies, including alloying, nano-sizing, doping with transition metals and their compounds, and using carbon-based materials as carriers. In particular, doping with transition metals and their compounds has been shown to effectively improve the hydrogen storage performance of magnesium-based materials, which may be the key to promoting the development of hydrogen energy technology.

[0004] In short, hydrogen energy is a promising solution to energy and environmental problems, and magnesium hydride has great potential as a hydrogen storage material, although it still requires technological breakthroughs to overcome existing challenges. Researchers are optimizing the performance of magnesium hydride through a variety of methods in order to achieve its high efficiency and stability in practical applications.

[0005] Based on this, this application was developed. Summary of the invention

[0006] The purpose of the present invention is to provide a magnesium-based composite hydrogen storage material based on NiV2S4 and magnesium hydride in view of the shortcomings of the current magnesium hydride. The magnesium-based composite hydrogen storage material is a bimetallic sulfide and magnesium hydride composite hydrogen storage material, which can reduce the dehydrogenation temperature of magnesium hydride and reduce the agglomeration and growth of magnesium hydride particles during the cycle, thereby improving the material's cycle stability and hydrogen storage capacity retention.

[0007] The present invention also provides a preparation method and application of the above-mentioned magnesium-based composite hydrogen storage material based on NiV2S4 and magnesium hydride.

[0008] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme: A composite hydrogen storage material based on NiV2S4 and magnesium hydride is prepared by ball milling NiV2S4 and magnesium hydride; the NiV2S4 is directly prepared by a high-temperature hydrothermal method, and the NiV2S4 is a structure of nano-flower-like particles stacked.

[0009] The present invention provides a method for preparing the above-mentioned composite hydrogen storage material based on NiV2S4 and magnesium hydride, which comprises the following steps: 1) Disperse nickel chloride hexahydrate, sodium orthovanadate and thiourea uniformly in water, and then keep at 150℃-180℃ for 12-24 hours; 2) Cool down to room temperature, wash and dry the reactants to obtain NiV2S4; 3) Mix NiV2S4 and magnesium hydride by ball milling.

[0010] Specifically, in step 1), the molar ratio of nickel chloride hexahydrate, sodium orthovanadate and thiourea can be 1:1.5-2.5:3.5-5.

[0011] Specifically, in step 2), drying is performed under vacuum conditions at 45°C-60°C for 12-24 h.

[0012] Specifically, in step 3), the prepared double transition metal sulfide NiV2S4 and magnesium hydride can be ball-milled at a mass ratio of 0.05-0.1:0.95-0.9.

[0013] Furthermore, in step 3), during the ball milling process, the ball-to-material ratio can be 30-50:1; the rotation speed can be 300-550 rpm / min. It is suitable to perform ball milling in a hydrogen environment. During the ball milling process, the ball milling time can be 3-6 h; in order to prevent cold welding during the ball milling process, the ball mill is stopped for 5-15 min after every 20-40 min of rotation. Preferably, the ball mill is stopped for 10 min after every 30 min of rotation.

[0014] The present invention also provides a composite hydrogen storage material based on NiV2S4 and magnesium hydride prepared by the above preparation method. For subsequent performance testing, the obtained NiV2S4-MgH2 composite hydrogen storage material can be stored in a glove box filled with argon atmosphere.

[0015] The present invention also provides the use of the above-mentioned NiV2S4 and magnesium hydride composite hydrogen storage material in hydrogen storage. The composite hydrogen storage material has a hydrogen release capacity of 6.1 wt% in 10 min at 290 °C, a hydrogen absorption capacity of 4.8 wt% in 20 min at 150 °C, and a capacity greater than 90% after 60 cycles at 300 °C.

[0016] The purpose of the present invention is to provide a composite hydrogen storage material based on NiV2S4 and magnesium hydride and its preparation and application. The composite hydrogen storage material provided by the present invention has good hydrogen storage performance and can be applied to the fields of catalysts, hydrogen storage materials, etc. Compared with the prior art, the present invention has the following advantages and beneficial effects: 1) The raw materials used in the preparation process of the composite hydrogen storage material of the present invention are available in the market at a relatively low price. The preparation method provided by the present invention is relatively simple, easy to operate, and has a short experimental cycle.

[0017] 2) The flower-shaped NiV2S4 synthesized by the present invention significantly improves the hydrogen storage performance of magnesium hydride. Analysis shows that the best effect on the hydrogen absorption and desorption performance of MgH2 is achieved when 5wt% NiV2S4 catalyst is added. The dehydrogenation starting temperature of the MgH2-5NiV2S4 composite material is 227℃, and hydrogen is almost completely released at 320℃, which is much lower than the desorption temperature of MgH2.

[0018] 3) With the addition of NiV2S4 catalyst, the hydrogen absorption and desorption kinetics and cyclability of MgH2 are greatly improved. At 350°C, the hydrogen desorption amount reaches 6.21 wt% in 5 minutes, and at 150°C, the hydrogen absorption amount reaches 4.8 wt% in 20 minutes. After 60 cycles at 300°C, the capacity is greater than 90%. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is the XRD spectrum of NiV2S4 in Example 1 of the present invention; Figure 2 This is a SEM picture of NiV2S4 in Example 1 of the present invention; Figure 3 TPD curves of commercial MgH2, ball-milled MgH2, MgH2-5 NiV2S4, MgH2-8 NiV2S4, and MgH2-10 NiV2S4 composite materials in the embodiments of the present invention; Figure 4 is the isothermal dehydrogenation curve of the MgH2-5 NiV2S4 composite material and MgH2 at 350°C in Example 2 of the present invention; Figure 5 The isothermal hydrogen absorption curves of the MgH2-5 NiV2S4 composite material and MgH2 at different temperatures in Example 2 of the present invention; Figure 6 This is the cycle curve of the MgH2-5 NiV2S4 composite material at 300°C in Example 2 of the present invention. DETAILED DESCRIPTION

[0020] The technical solution of the present invention will be described in detail below through specific embodiments, but it should be emphasized that the protection scope of the present invention is not limited to the specific embodiments described below.

[0021] In the following examples, unless otherwise specified, the raw materials used are common commercial products that can be directly purchased on the market, or can be prepared by conventional technical methods in the art.

[0022] The room temperature mentioned in the text refers to 25±5℃.

[0023] Embodiment 1: The preparation method of NiV2S4 is specifically implemented as follows: First, 5 mmol of nickel chloride hexahydrate, 10 mmol of sodium orthovanadate and 20 mmol of thiourea were added to 80 mL of deionized water (molar ratio of 1:2:4), and dispersed evenly by ultrasonication for 30 min. Then the solution was transferred to a stainless steel autoclave with a Teflon liner and kept at 170 ° C for 18 h. After the reaction was completed, it was naturally cooled to room temperature. The reactants were washed with deionized water and ethanol by centrifugation for 3 times at room temperature, and then dried in a vacuum oven at 60 ° C for 12 h to obtain the catalyst NiV2S4.

[0024] Embodiment 2: The prepared NiV2S4 and MgH2 powders were ball milled at a mass ratio of 0.05:0.95 for 4 hours, the vacuum ball mill was kept in a hydrogen atmosphere, the ball-to-material ratio was 40:1, the rotation speed was 400 rpm / min, and the ball mill was stopped for 10 minutes after every 30 minutes of rotation. The MgH2-5 NiV2S4 composite hydrogen storage material was obtained by ball milling and mixing.

[0025] For subsequent performance testing, the prepared MgH2-5 NiV2S4 composite hydrogen storage material was stored in a glove box filled with argon atmosphere.

[0026] Embodiment 3: The prepared NiV2S4 and MgH2 powders were ball milled at a mass ratio of 0.08:0.92 for 4 hours, the vacuum ball mill was kept in a hydrogen atmosphere, the ball-to-material ratio was 40:1, the rotation speed was 400 rpm / min, and the ball mill was stopped for 10 minutes after every 30 minutes of rotation. The MgH2-8 NiV2S4 composite hydrogen storage material was obtained by ball milling and mixing.

[0027] For subsequent performance testing, the obtained MgH2-8 NiV2S4 composite hydrogen storage material was stored in a glove box filled with argon atmosphere.

[0028] Embodiment 4: The prepared NiV2S4 and MgH2 powders were ball-milled at a mass ratio of 0.1:0.9 for 4 hours, the vacuum ball mill was kept in a hydrogen atmosphere, the ball-to-material ratio was 40:1, the rotation speed was 400 rpm / min, and the ball mill was stopped for 10 minutes after every 30 minutes of rotation. The MgH2-10 NiV2S4 composite hydrogen storage material was obtained by ball milling and mixing.

[0029] For subsequent performance testing, the obtained MgH2-10 NiV2S4 composite hydrogen storage material was stored in a glove box filled with argon atmosphere.

[0030] Embodiment 5: The preparation method of NiV2S4 is specifically implemented as follows: First, 5 mmol of nickel chloride hexahydrate, 12 mmol of sodium orthovanadate and 25 mmol of thiourea were added to 60 mL of deionized water (molar ratio of 1:2.4:5) and dispersed evenly by ultrasonication for 30 min. Then the solution was transferred to a stainless steel autoclave with a Teflon liner and kept at 170 °C for 20 h. After the reaction was completed, it was naturally cooled to room temperature. The reactants were washed with deionized water and ethanol by centrifugation for 3 times at room temperature, and then dried in a vacuum oven at 50 °C for 12 h to obtain the catalyst NiV2S4.

[0031] Performance measurement First, the double transition metal sulfide NiV2S4 synthesized in Example 1 was characterized by XRD and SEM. Figure 1 , 2 The XRD spectrum and SEM image of NiV2S4 in Example 1 of the present invention are given respectively. Figure 1 and Figure 2 The results show that the present invention successfully prepared a flower-like NiV2S4 catalyst, which has a structure of nano-flower-like particles stacked with a particle size of 500-800 nm.

[0032] In order to explore the effect of adding NiV2S4 on magnesium hydride, isothermal programmed desorption (TPD) experiments were carried out on MgH2 and the three ratio composite hydrogen storage materials of Examples 2, 3, and 4. The TPD heating rate was 2°C / min. The results are shown in Figure 3 .from Figure 3 It can be seen that the initial dehydrogenation temperature of ball-milled MgH2 is 365°C, the initial dehydrogenation temperature of MgH2-5 NiV2S4 composite hydrogen storage material is 227°C, and the addition of NiV2S4 catalyst reduces the initial dehydrogenation temperature of MgH2 by 138°C. Figure 3 As shown, adding 5wt.% NiV2S4 has the best effect.

[0033] In order to explore the effect of adding NiV2S4 on the hydrogen absorption and desorption performance of magnesium hydride, the isothermal dehydrogenation performance and isothermal hydrogen absorption performance experiments were carried out on the MgH2-5NiV2S4 composite hydrogen storage material (addition 5wt.%). The results are shown in Figure 4 and Figure 5 .

[0034] Figure 4The isothermal dehydrogenation curve of the MgH2-5 NiV2S4 composite hydrogen storage material and MgH2 at 350°C in Example 2 of the present invention is given. Figure 4 It can be seen that the MgH2-5 NiV2S4 composite hydrogen storage material can release 6.21wt.% of hydrogen at 350℃ for 5 min, and the dehydrogenation is basically completed within 5 min, while MgH2 can only release 1.5wt.% of hydrogen at this temperature for 30 min. The results show that the doping of NiV2S4 has a significant improvement on the dehydrogenation performance of MgH2.

[0035] Figure 5 The isothermal hydrogen absorption curves of the MgH2-5 NiV2S4 composite hydrogen storage material and MgH2 at different temperatures in Example 2 of the present invention are given. Figure 5 It can be seen that at 150°C, the hydrogen absorption of the MgH2-5 NiV2S4 composite hydrogen storage material reaches 4.5wt.% within 10 minutes, and the hydrogen absorption reaches 4.8 wt% in 20 minutes. If MgH2 wants to absorb 4.5wt% of hydrogen, it needs to be at a high temperature of 350°C. The results show that adding NiV2S4 can greatly improve the hydrogen absorption kinetics of the composite material at low temperatures.

[0036] Figure 6 The isothermal cycle curve of the MgH2-5 NiV2S4 composite material at 300°C in Example 2 of the present invention is given. Figure 6 As shown, the first dehydrogenation amount is 5.98wt.%, while the 60th dehydrogenation amount is 5.47wt.%, and the dehydrogenation capacity retention rate is 91.47%, indicating that the MgH2-5 NiV2S4 composite hydrogen storage material has good cycle stability performance.

[0037] In summary, the hydrogen storage material provided by the present invention exhibits excellent performance, which has an extremely important impact on promoting the advancement and practical application of magnesium-based hydrogen storage technology. Through optimization and improvement, the present invention not only improves the hydrogen storage efficiency, but also enhances the cyclic stability of the material, which are key factors in realizing the commercialization of hydrogen energy technology. Therefore, the present invention has great potential value in promoting clean energy transformation and solving the energy crisis.

[0038] Although the above embodiment shows a recommended implementation of the present invention, it does not limit the scope of protection of the present invention. Any minor adjustments, innovations or substitutions made within the framework of the present invention, as long as these changes do not deviate from the core concept and technical solution of the present invention, should be regarded as part of the protection of the present invention.

Claims

1. A composite hydrogen storage material based on NiV2S4 and magnesium hydride, characterized in that: It is prepared by ball milling NiV2S4 and magnesium hydride; the NiV2S4 is prepared by a hydrothermal method, and the NiV2S4 is a structure of nano-flower-like particles stacked.

2. The method for preparing the composite hydrogen storage material based on NiV2S4 and magnesium hydride according to claim 1, characterized in that: The following steps are involved: 1) Disperse nickel chloride hexahydrate, sodium orthovanadate and thiourea in water and then keep at 150℃-180℃ for 12-24 hours; 2) Cool to room temperature, wash and dry to obtain NiV2S4; 3) Mix NiV2S4 and magnesium hydride by ball milling.

3. The method for preparing a composite hydrogen storage material based on NiV2S4 and magnesium hydride as claimed in claim 2, characterized in that: In step 1), the molar ratio of nickel chloride hexahydrate, sodium orthovanadate and thiourea is 1:1.5-2.5:3.5-5.

4. The method for preparing a composite hydrogen storage material based on NiV2S4 and magnesium hydride as claimed in claim 2, characterized in that: In step 2), drying is performed under vacuum conditions at 45 °C-60 °C for 12-24 h.

5. The method for preparing a composite hydrogen storage material based on NiV2S4 and magnesium hydride as claimed in claim 2, characterized in that: In step 3), the prepared NiV2S4 and magnesium hydride are ball-milled at a mass ratio of 0.05-0.1:0.95-0.

9.

6. The method for preparing a composite hydrogen storage material based on NiV2S4 and magnesium hydride as claimed in claim 5, characterized in that: In step 3), during the ball milling process, the ball-to-material ratio is 30-50:1; the rotation speed is 300-550 rpm / min.

7. The method for preparing a composite hydrogen storage material based on NiV2S4 and magnesium hydride as claimed in claim 5, characterized in that: In step 3), ball milling is performed under a hydrogen environment.

8. The method for preparing a composite hydrogen storage material based on NiV2S4 and magnesium hydride as claimed in claim 5, characterized in that: In step 3), the ball milling time is 3-6 h; during the ball milling process, the ball mill rotates for 20-40 min and stops for 5-15 min.

9. A composite hydrogen storage material based on NiV2S4 and magnesium hydride prepared by the preparation method according to any one of claims 2 to 8.

10. Use of the composite hydrogen storage material based on NiV2S4 and magnesium hydride according to claim 1 or 9 in hydrogen storage.

Citation Information

Patent Citations

  • Sulfur-rich vanadium-modified NiS2 electrocatalyst and preparation method thereof

    CN109277104A

  • Solid magnesium-based hydrogen storage material MgH2-MnV2O6 and preparation method thereof

    CN114684784A

  • Bimetal sulfide composite magnesium-based hydrogen storage material and preparation method thereof

    CN115159452A

  • MgH2 composite material based on hydrangea-shaped NiO / KNbO3 as well as preparation method and application of MgH2 composite material

    CN116462156A

  • Bimetal nitride catalyst as well as preparation method and application thereof

    CN116786151A